Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the equation y’’=(3-y)(2-y)

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$y_1=2,\:y_2=3$

Step-by-step explanation

Problem to solve:

$y’’=\left(3-y\right)\left(2-y\right)$
1

The product of two binomials of the form $(x+a)(x+b)$ is equal to the product of the first terms of the binomials, plus the algebraic sum of the second terms by the common term of the binomials, plus the product of the second terms of the binomials. In other words: $(x+a)(x+b)=x^2+(a+b)x+ab$

$y’’=y^2-5y+6$
2

Grouping terms

$y’’-y^2-1-5y=6$

Unlock this step-by-step solution!

Answer

$y_1=2,\:y_2=3$
$y’’=\left(3-y\right)\left(2-y\right)$

Main topic:

Polynomials

Time to solve it:

~ 0.94 seconds

Struggling with math?

Access detailed step by step solutions to millions of problems, growing every day!